Intergenerational Patterns in Beliefs About Women's Roles Among Adolescents and Their Parents in the Czech Republic - Shebloski, Barbara and Gibbons, Judith L. (Cross-Cultural Research, 1998)
Sixty-nine dyads consisting of an adolescent (age 15 or 16) and his or her parent living in the Polish-speaking region of the Czech Republic completed the adolescent or short version of the Attitudes Toward Women Scale (Galambos, Petersen, Richards, & Gitelson, 1985; Spence, Helmreich, & Stapp, 1973). The attitudes of parents and their adolescent children were significantly correlated, and the younger generation expressed less traditional attitudes than did their parents. In addition, mothers and adolescent girls held more egalitarian (less traditional) beliefs than did their male counterparts. These results suggest that attitudes toward women's roles may be becoming less traditional in the Czech Republic as in other parts of the world and that even in a rapidly changing society, parents and their adolescent children share beliefs about appropriate gender roles.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDY5Mzk3MTk4MDMyMDAzMDM